Female engagement in commercial agriculture, interventions and welfare in Malawi: What works for the poorest? - Ralitza Dimova; Ira N. Gang (Rutgers University, Department of Economics, 2015)
The poverty and extreme poverty alleviating potential of female empowerment through agricultural commercialisation has been an increasing focus of much of the recent development literature and policy discourse. Using representative data from Malawi, this chapter looks at the role of key policy interventions on the probability for women to enter the commercial agricultural sector and the impact of agricultural commercialisation on poverty and extreme poverty. We find that (i) Most interventions had positive impact on female food commercialisation, but either did not affect or affected negatively female entry into high value agriculture, (ii) Female empowerment through high value agriculture benefitted the poor and extreme poor. We conclude that gender norms in food commercialisation and high value agriculture should be understood for female empowerment interventions of the type implemented in Malawi to have the desired effect.
Keywords: 330; female empowerment; commercial agriculture; policy interventions; Malawi